Choice Recommendations for Rational Concreting Technology of Steel Reinforced Concrete Structures - Nikiforova, Ð¢atiana; Gukasian, Olga; Mahas, Nataliia (International Journal of Engineering and Technology, 2018)
In this work the experimental research cycle is described. This cycle is an affect studying of the most widespread concrete defect types, such as concrete core weakening is an inclusion of the "weak" concrete, the presence of emptiness, concrete heterogeneous by the height. The research of the manufacturing conditions affect of combine concrete core structures and the elements of physical and mechanical characteristics changing are on the experimental research base. On the researches testing base of samples with special form and given sizes the concrete strength value is appreciated. The different variants of strength decreasing on the researched element height are analyzed by the conducted testing results of the steel reinforced concrete structures. As a result of the conducted tests, the work conditions coefficient and the steel reinforced concrete elements concreting technology were formulated.Â Â